2019
DOI: 10.1038/s41598-019-38715-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between Poor Sleep Quality and Subsequent Peptic Ulcer Recurrence in Older Patients with Mild Cognitive Impairment: Examining the Role of Social Engagement

Abstract: This study aims to examine whether perceived poor sleep quality predicts subsequent recurrence of peptic ulcer disease (PUD) in older patients with mild cognitive impairment following Helicobacter pylori eradication and to investigate whether social engagement status alters this association. Of 1,689 older patients with H. pylori-infected PUD recruited from eight Grade-A hospitals in the People’s Republic of China between 2011 and 2014, H. pylori was eradicated and PUD cleared in 1,538 patients by the end of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Peptic ulcer disease (PUD) is best defined as a peptic injury of the alimentary tract that occurs in the stomach or the proximal duodenum, as a secondary to the damaging effects of pepsin, active free radicals, oxidants, leukotrienes, endothelins, and stomach acid secretion. This subsequently leads to a mucosal defect reaching the submucosa or muscularis propria [1,2]. The estimated prevalence of PUD in the general population is approximately 4.1%, and 10% of people develop PUD during the course of a lifetime [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulcer disease (PUD) is best defined as a peptic injury of the alimentary tract that occurs in the stomach or the proximal duodenum, as a secondary to the damaging effects of pepsin, active free radicals, oxidants, leukotrienes, endothelins, and stomach acid secretion. This subsequently leads to a mucosal defect reaching the submucosa or muscularis propria [1,2]. The estimated prevalence of PUD in the general population is approximately 4.1%, and 10% of people develop PUD during the course of a lifetime [3].…”
Section: Introductionmentioning
confidence: 99%
“…PUD is a chronic inflammatory disease; insomnia is closely related to gastroesophageal reflux and peptic ulcer [ 15 ]. Clinical studies have found that patients with poor sleep quality have a higher recurrence rate of PUD [ 8 ]. Despite observational studies indicate an association between insomnia and PUD, it is lacking of causal evidence for effects of insomnia on PUD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study found that among women, those who slept less than seven hours a night had twice the risk of developing PUD compared to those who slept more than nine hours a night [ 7 ]. Another study investigated whether poor sleep quality predicted recurrence of PUD in 1,538 elderly patients who had been inoculated with H. pylori; the result shows that the recurrence rate of PUD was higher in poor sleepers than in good sleepers [ 8 ]. With the deepening of the research on peptic ulcer, scholars believe that there is a certain correlation between sleep quality and peptic ulcer, which is both the cause of the disease and the rehabilitation disorder.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that poor sleep quality was a predictor of increased risk for the recurrence of PUD and should be taken into account at least in elderly patients. They also showed that continued social involvement reduced the risk of poor sleeping with the consequence of alignment of the recurrence rate of PUD in the poor and good sleepers . Pathophysiologic explanations are speculative at this moment.…”
Section: Gastric Diseasesmentioning
confidence: 95%